A new policy paradigm from the traditional counter terrorist measures to address the menace of ideological extremism in India - Samraj, P. Lazarus; Saravanan, J. (2010)
One of the major reasons for the escalation of ideological extremism in certain regions of India is the successive governments' failure to share the cake of development with the tribal people and the continuous exploitation of their resources by outsiders, depriving them to their traditional livelihoods and basic facilities. The socially and economically deprived people who are ideologically indoctrinated cannot be tamed or reformed or forced to join the mainstream through the negative means adopted by the law enforcing agencies. There is a vast rural and tribal population living without any primary school, water tank, health facility, electricity and roads. Who is responsible for their pitiable condition after 60 plus year of Independence? To overcome their violent agenda the state and the Central governments should formulate strategies to implement developmental approach, which concentrate on the inclusive and multifaceted development plans to address the socio-economic needs of the deprived people. - Reproduced.
Keywords: Terrorism - India; Terrorism